Konsep Teologi Hasan Hanafi - Syarifuddin Syarifuddin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2012)
Hasan Hanafi is a modernist scholar whose ideas focus on renewing and  reconstructing Islam. These ideas can be witnessed through his great concept on  al-Turats wa al-Tajdid (Tradition and renewal) and Al-Yasar al Islam (left Islam), both were publicized in 1981. These concepts are interpretation and renewed form  of Jamaluddin‟s and Muhmmad Abduh‟s al Urwatul Wutsq. Hasan Hanafi argues  that theology as a science acts as deed analytical tool, while social knowledge is  applications of faith system. In his analysis, tradition is not fixed form of deed and  past institutions. It is representing the concept of prescriptive norms from  developing faith traditions, which constantly under construction process. Hasan  Hanafi‟s theological concept is in line with ideas of humanities, union, populism,  justice, and social stability. As if, in his hand theology is understood as a protest,  social critic, and revolution that focus on human understanding on the historical  reality of humanity, which has been proceeded for centuries.